Communicative Activities Based on Competence Standard of 2013 Curriculum - Affandi, Yusna (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
For upcoming academic years, senior high schools in Indonesia are implementing a new curriculum, 2013 curriculum. It is stated in the curriculum that English is taught as a language of international communication. Therefore, the English instruction should provide students to enhance their communicative competence. It emphasizes on speaking skill which students acquire for communication. This article proposes three communicative activities based on competence standard of 2013 curriculum to enhance students’ communicative competence. The communicative activities are information-gap activities, task completion activities, and information gathering activities. The focus of proposed communicative activities is on improving students’ speaking skill.